Development of online class with the implementation of a hybrid system in the entrepreneurship learning of vocational high schools in Surabaya - Adham Afif Darmawan; Raya Sulistyowati (Sean Institute, 2024)
The Internet has had many impacts on the world of education. With the convenience of the internet, students tend to experience a lack of interest in learning. This study aimed to determine the application of hybrid system learning in the entrepreneurship learning of the Ketintang Vocational High School Surabaya. The population used was all students in the eleventh grade class, with a sample of 72 students using purposive sampling. The research analysis method used linear regression with the IBM SPSS 26 application. Hybrid system learning had a positive and significant effect, with a strong influence of 68.2%. The results of this study can be used by Ketintang Vocational High School Surabaya to maintain the quality of learning so that it remains effective with the hybrid system.